(untitled) (gjstudies, 2021)
This research investigates the complex ethical terrain navigated by accounting professionals operating within increasingly competitive market landscapes. While existingliterature often frames ethical dilemmas in accounting through the lens of regulatorycompliance or individual moral failure, this study proposes a novel conceptual framework that situates these dilemmas within the structural and psychological pressuresgenerated by market competition itself. We argue that competition does not merelycreate occasions for ethical lapses but actively reshapes the cognitive and normativeframeworks through which accountants perceive their professional duties. The studyemploys a mixed-methods approach, combining a quantitative survey of 347 certifiedpublic accountants across various sectors with in-depth, phenomenological interviewswith 42 senior accounting professionals. This methodological triangulation allows us tomove beyond identifying common dilemmas to modeling the decision-making processesunder competitive duress. Our findings reveal a previously under-theorized categoryof ’systemic ethical stress,’ where the imperative to retain clients and ensure firm viability directly conflicts with strict adherence to professional standards of objectivityand conservatism. Notably, the results demonstrate that the intensity of perceivedethical conflict is not linearly correlated with the degree of market competition butfollows a threshold model, with significant escalation occurring after competitive pressures surpass a certain point of firm resource strain. Furthermore, the research identifies’competitive neutralization’ as a key cognitive mechanism, whereby professionals rationalize ethically ambiguous actions as necessary strategic responses rather than ethicalcompromises. The paper concludes by proposing a revised model of ethical resiliencefor accounting practice, emphasizing structural safeguards and collective professionalnorms over individual character, offering a significant departure from predominant,agent-centric ethical training models. This contribution provides a new theoreticalfoundation for understanding professional ethics in business contexts where commercial and fiduciary imperatives are in constant tension